The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11403-007-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of the level of cooperation in the presence of punishment in three public good experiments

Abstract: Strong reciprocity is a fundamental human characteristic associated with our extraordinary sociality and cooperation. Laboratory experiments on social dilemma games and many field studies have quantified well-defined levels of cooperation and propensity to punish/reward. The level of cooperation is observed to be strongly dependent on the availability of punishments and/or rewards. Here, we propose an operational approach based on the evolutionary selection of prosocial behaviors to explain the quantitative le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…The percentages of acceptance for the five types of offers are depicted in Figure 4 . The acceptance/rejection ratios are in accordance with previous studies employing the repeated UG [39] [41] . A dramatic drop in the acceptance rate for offers around 20% or less of the amount to be split indicates that these offers were judged as unfair by our participants.…”
Section: Resultssupporting
confidence: 91%
“…The percentages of acceptance for the five types of offers are depicted in Figure 4 . The acceptance/rejection ratios are in accordance with previous studies employing the repeated UG [39] [41] . A dramatic drop in the acceptance rate for offers around 20% or less of the amount to be split indicates that these offers were judged as unfair by our participants.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, within-group cooperation might be maintained or enhanced by between-groups competition, although this is debated (Bowles (2006) argues in this sense but is contradicted by Langergraber et al (2011)). Finally, one of us implemented an ABM of a public good game with altruistic punishment and found that cooperation can thrive among selfish disadvantageous inequity averse agents (Hetzer and Sornette, 2009), a conclusion also supported by game theoretical calculations (Darcet and Sornette, 2008;Hetzer and Sornette, 2001). This suggests that competitive agents still find it advantageous to cooperate in order to achieve their goals.…”
Section: Discussionmentioning
confidence: 77%
“…Note that the value of the mode around k = 0.2 is close to the slope of the straight line fitting the empirical data shown in figure 1 providing another confirmation of the explanatory power of our ABM. This most probable value k = 0.2 has also been obtained analytically by assuming an evolutionary optimization of the expected gains with respect to potential future losses due to punishment [34].…”
Section: The Emergence Of Altruistic Punishmentmentioning
confidence: 89%